Charting the Sino-Latin Nexus: A Comprehensive Exploration of Academic Literature between China and Latin America - Chavarría Camacho , David (2024)
This study provides a comprehensive review of academic literature on the relationship between China and Latin America, identifying key themes such as diplomacy, economic and technological cooperation, and cultural exchanges. Through a qualitative analysis of academic production, it explores the evolutionary phases of this relationship and its implications for both regions. The review highlights both the achievements and challenges of Sino-Latin cooperation and suggests directions for future research to promote beneficial and sustainable collaboration.